2016
DOI: 10.1002/hbm.23085
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low‐dose ketamine on the prefrontal cortex and amygdala in treatment‐resistant depression: A randomized controlled study

Abstract: Ketamine's rapid antidepressant effects involved the facilitation of glutamatergic neurotransmission in the PFC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 45 publications
4
80
0
1
Order By: Relevance
“…Many reports have showed that CSDS induces molecular and circuit abnormalities including alterations in BDNF-TrkB signaling, ΔFosB signaling, and prefrontal cortexamygdala circuitry [63,65,72], consistent with studies of MDD patients [73][74][75][76]. Importantly, CSDS mice also respond to the rapid-acting antidepressant ketamine [47,77,78], which is known to be efficacious even in treatment-resistant patients and to depend on alterations in glutamate homeostasis [79][80][81]. Thus, while CSDS mice are not exclusively a model of treatmentresistant depression, they do exhibit predictive validity for one of the few pharmacotherapies effective at treating refractory depression through a mechanism distinct from monoaminergic agents.…”
Section: Discussionsupporting
confidence: 60%
“…Many reports have showed that CSDS induces molecular and circuit abnormalities including alterations in BDNF-TrkB signaling, ΔFosB signaling, and prefrontal cortexamygdala circuitry [63,65,72], consistent with studies of MDD patients [73][74][75][76]. Importantly, CSDS mice also respond to the rapid-acting antidepressant ketamine [47,77,78], which is known to be efficacious even in treatment-resistant patients and to depend on alterations in glutamate homeostasis [79][80][81]. Thus, while CSDS mice are not exclusively a model of treatmentresistant depression, they do exhibit predictive validity for one of the few pharmacotherapies effective at treating refractory depression through a mechanism distinct from monoaminergic agents.…”
Section: Discussionsupporting
confidence: 60%
“…In healthy subjects, functional connectivity between the rACC and mPFC increased acutely (95) and decreased 24 hours after ketamine infusion (96). Furthermore, using PET imaging methods, ketamine associated with increased glucose metabolism in the dorsal ACC (dACC) (97), altered glucose metabolism in PFC regions (9799) in MDD, and increased glucose metabolism in the dACC and putamen in BD patients (100). Our group has shown that sgACC hypermetabolism predicted response to ketamine in BD patients (101).…”
Section: Ketamine and Functional Neural Circuitry In Depressionmentioning
confidence: 99%
“…Cortical Excitation. Though competing explanations for the rapid antidepressant effects of ketamine have been proposed, most converge on the idea that subanesthetic (i.e., antidepressant) doses of ketamine lead to widespread cortical excitation and increases in energy metabolism (Breier et al, 1997;Lu et al, 2008;Li et al, 2016a;Abdallah et al, 2018a) (Fig. 2).…”
Section: Examining Rapid Antidepressant Effects Through Encodingmentioning
confidence: 99%